Preparation method and application of zinc-dipped aluminum foil negative electrode applied to lithium ion battery

By forming a dense zinc layer on the surface of the aluminum foil, the problem of insufficient conductivity and structural stability of the aluminum foil negative electrode material is solved, and the circulation performance and Coulomb efficiency of the lithium-ion battery are significantly improved.

CN119581499AActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411789564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

As a negative electrode material for lithium-ion batteries, aluminum foil has poor conductivity and structural stability, mainly due to the presence of its surface oxide layer and the volume changes in the alloying/dealloying process.

Method used

The aluminum is protected from oxidation by immersing the aluminum foil in the sodium hydroxide solution and then immersing it in the zinc impregnation solution containing zinc oxide and additives to form a dense zinc layer.

Benefits of technology

The high conductivity, corrosion resistance and structural stability of the aluminum foil negative electrode are achieved, and the circulation performance and first-circuit Coulomb efficiency of the lithium-ion battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581499A_ABST
    Figure CN119581499A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a zinc-dipped aluminum foil negative electrode applied to a lithium ion battery, and belongs to the field of lithium ion batteries. The zinc-dipped aluminum foil is prepared aiming at the defects and deficiencies of the aluminum foil serving as a lithium ion battery negative electrode material; the zinc-dipped aluminum foil negative electrode prepared by the method is flat and bright, has good corrosion resistance and high conductivity, and has the advantages of low impedance, high charge-discharge rate, high first-circle coulombic efficiency, small hysteresis phenomenon and the like when being assembled with a lithium foil to form a half battery. The method comprises the following steps: 1, pretreating aluminum foil; 2, preparing a zinc dipping solution; and 3, zinc immersion treatment. The zinc-dipped aluminum foil negative electrode applied to the lithium ion battery is used as a negative electrode of the lithium ion battery. Compared with a half cell assembled by a traditional aluminum foil electrode, the zinc-dipped aluminum foil electrode has higher charge-discharge rate and lower impedance, and also has higher first-circle coulombic efficiency and more stable cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a preparation method and application of a zinc-impregnated aluminum foil negative electrode for lithium ion batteries. Background Art

[0002] As the most abundant metal element in the earth's crust, aluminum has outstanding advantages such as no pollution and low cost. It can be used at low potentials (~0.2V and ~0.4V vs. Li 0 / Li + ) for lithium insertion and extraction, and has a larger theoretical specific capacity than graphite (993 mAhg -1 ). Therefore, aluminum is an attractive negative electrode material for lithium-ion batteries. Kuksenko proposed [Russ. J. Electrochemistry, 2013, Vol. 49, No. 1, pp. 67–75] to use aluminum foil as an "ideal negative electrode material for lithium-ion batteries". However, due to the presence of an oxide layer on the surface of the aluminum foil negative electrode and the non-negligible volume change during the alloying / de-alloying process, the aluminum foil negative electrode has poor conductivity and structural stability, which seriously limits the further application of aluminum-based negative electrodes in lithium-ion batteries. Therefore, it is necessary to explore new research methods to further improve the electrochemical performance of aluminum-based negative electrodes.

[0003] Due to the high reactivity of metallic aluminum, a layer of non-conductive aluminum oxide is easily formed on its surface, which causes the negative electrode of the metal aluminum foil to be in a passivated state. In addition, due to the poor electrical conductivity of aluminum oxide and the irreversible consumption of lithium in the process of forming the SEI film, the battery capacity will decay rapidly and the initial coulombic efficiency will be poor. Therefore, the oxide layer on the surface of the aluminum foil not only hinders the transmission rate of lithium ions, but also reduces the initial coulombic efficiency [H.Wang, H.Tan, X.Luo, H.Wang, T.Ma, M.Lv, X.Song, S.Jin, X.Chang, X.Li, J.Mater.Chem.A 2020, 8, 25649]. The irreversible lithium loss during the alloying process causes the unreacted aluminum oxide surface layer to be preferentially alloyed along the rolling direction of the aluminum foil until the entire surface is covered with Li. x AlO yCovering [D.Li, F.Chu, Z.He, Y.Cheng, F.Wu, Single-material aluminum foil asanodes enabling high-performance lithium-ion batteries: The roles of prelithiation and working mechanism, Materials Today, https: / / doi.org / 10.1016 / j.mattod.2022.07.004]. The research of Tahmasebi et al. shows [MHTahmasebi, D.Kramer, R. ST Boles, J. Electrochem. Soc. 2019, 166, A5001], the lithiation of aluminum begins with the nucleation of the surface β-LiAl phase, and these nucleation areas continue to expand until these areas are connected. Due to the presence of the aluminum oxide layer, the alloying reaction between the aluminum surface and lithium is extremely uneven. It can be seen that solving the problem of aluminum oxide plays an important role in realizing the practical application of aluminum-based negative electrode materials in lithium-ion batteries. However, there is currently no effective solution to the problem of removing aluminum oxide from the aluminum surface. Therefore, the present invention proposes a simple and effective method to remove the oxide layer on the aluminum surface, that is, while removing the aluminum oxide, a dense zinc layer is formed in situ to protect the aluminum from being oxidized again, thereby achieving high cycle performance in lithium-ion batteries. Summary of the invention

[0004] Aiming at the shortcomings and deficiencies of the above-mentioned aluminum foil as a negative electrode material for lithium ion batteries, the present invention provides a preparation method and application of a zinc-impregnated aluminum foil negative electrode for lithium ion batteries.

[0005] The zinc-impregnated aluminum foil negative electrode prepared by the method of the present invention is smooth and bright, has good corrosion resistance and high conductivity, and is assembled into a half-cell with lithium foil, which has the advantages of low impedance, high charge and discharge rate, high first-cycle coulomb efficiency and small hysteresis phenomenon.

[0006] The present invention provides a method for preparing a zinc-impregnated aluminum foil negative electrode for a lithium-ion battery, which is specifically completed by the following steps:

[0007] 1. Pretreatment of aluminum foil:

[0008] The aluminum foil is immersed in a sodium hydroxide solution for a period of time, and then taken out and washed with water until it is neutral to remove the oxide layer on the surface of the aluminum foil to obtain a pretreated aluminum foil;

[0009] 2. Preparation of zinc immersion solution:

[0010] Evenly mixing sodium hydroxide, zinc oxide, additives and water to obtain a zinc dipping solution;

[0011] 3. Zinc treatment:

[0012] The pretreated aluminum foil is immersed in a zinc dipping solution for a period of time, taken out, washed with water, and dried to obtain a zinc-dipped aluminum foil negative electrode for lithium-ion batteries.

[0013] A zinc-impregnated aluminum foil negative electrode applied to a lithium-ion battery is used as the negative electrode of the lithium-ion battery.

[0014] Advantages of the present invention:

[0015] Compared with the zinc-impregnated aluminum foil prepared without adding additives, the zinc-impregnated aluminum foil prepared by the present invention has stronger bonding force between the zinc layer and the aluminum foil matrix, better corrosion resistance and better wettability to the electrolyte; the zinc-impregnated aluminum foil negative electrode and lithium foil prepared by the present invention are applied to lithium-ion batteries to achieve higher rate performance, lower impedance and smaller hysteresis; in addition, since the oxide layer on the surface of the aluminum foil is removed, lithium will not be consumed due to its reduction, and the aluminum foil after zinc immersion has higher wettability to the electrolyte, which can significantly improve the rate capacity of the aluminum foil electrode; it is particularly noteworthy that, in the absence of pre-lithiation, compared with the half-cell assembled by the traditional aluminum foil electrode, the zinc-impregnated aluminum foil electrode has a higher charge and discharge rate and lower impedance, and also has a higher first-cycle coulomb efficiency and more stable cycle performance.

[0016] In summary, the zinc-impregnated aluminum foil negative electrode prepared by the present invention has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The morphology of the zinc-impregnated aluminum foil negative electrode and the traditional aluminum foil negative electrode prepared using the additive in Example 1 under an optical microscope;

[0018] Figure 2 The morphology of the zinc-impregnated aluminum foil negative electrode prepared with the additive in Example 2 and the zinc-impregnated aluminum foil negative electrode prepared without the additive in Comparative Example 1 under a scanning electron microscope;

[0019] Figure 3 The half-cell assembled with the zinc-impregnated aluminum foil negative electrode prepared using the additive in Example 1 was 2 and 2.0mAh / cm 2 Cyclic performance curve under capacity load;

[0020] Figure 4 The half-cell assembled with the zinc-impregnated aluminum foil negative electrode prepared with the additive of Example 2 and the conventional aluminum foil negative electrode at 0.5 mA / cm 2 and 2.0mAh / cm 2The charge and discharge curves and cycle performance curves under capacity load are shown in FIG. 1 ; in the figure, a and d are half-cells assembled using traditional aluminum foil, b and e are half-cells assembled using zinc-impregnated aluminum foil without additives in Comparative Example 1, and c and f are half-cells assembled using zinc-impregnated aluminum foil prepared in Example 2. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a zinc-impregnated aluminum foil negative electrode for a lithium-ion battery, which is specifically completed by the following steps:

[0022] 1. Pretreatment of aluminum foil:

[0023] The aluminum foil is immersed in a sodium hydroxide solution for a period of time, and then taken out and washed with water until it is neutral to remove the oxide layer on the surface of the aluminum foil to obtain a pretreated aluminum foil;

[0024] 2. Preparation of zinc immersion solution:

[0025] Evenly mixing sodium hydroxide, zinc oxide, additives and water to obtain a zinc dipping solution;

[0026] 3. Zinc treatment:

[0027] The pretreated aluminum foil is immersed in a zinc dipping solution for a period of time, taken out, washed with water, and dried to obtain a zinc-dipped aluminum foil negative electrode for lithium-ion batteries.

[0028] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the soaking time in step 1 is 20s to 40s. The other steps are the same as those in specific implementation method 1.

[0029] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the concentration of the sodium hydroxide solution in step 1 is 40 g / L to 50 g / L. The other steps are the same as those in specific implementation method 1 or 2.

[0030] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the temperature of the sodium hydroxide solution in step 1 is 80° C. The other steps are the same as those in specific embodiments 1 to 3.

[0031] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of sodium hydroxide in the zinc leaching solution in step 2 is 400 g / L to 500 g / L, the concentration of zinc oxide is 50 g / L to 100 g / L, and the concentration of the additive is 0.05 g / L to 5 g / L. The other steps are the same as those of specific embodiments 1 to 4.

[0032] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the additive in step 2 is a mixture of two or more of potassium sodium tartrate, karaya gum, sodium sulfonamide acetyl, β-cyclodextrin, azodicarbonamide and 4-hexylresorcinol. The other steps are the same as those of specific embodiments 1 to 5.

[0033] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the soaking time in step 3 is 2s to 40s. The other steps are the same as those in specific embodiments 1 to 6.

[0034] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the temperature of the zinc dipping solution in step 3 is 25° C. The other steps are the same as those in specific embodiments 1 to 7.

[0035] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the number of water washings in step 3 is 2 to 4 times; the drying temperature in step 3 is 60° C. and the drying time is 1 hour. The other steps are the same as those in specific embodiments 1 to 8.

[0036] Specific implementation method ten: This implementation method is a zinc-impregnated aluminum foil negative electrode used in lithium-ion batteries as the negative electrode of lithium-ion batteries.

[0037] The following examples are used to verify the beneficial effects of the present invention:

[0038] Example 1: A method for preparing a zinc-impregnated aluminum foil negative electrode for a lithium-ion battery is specifically completed by the following steps:

[0039] 1. Pretreatment of aluminum foil:

[0040] Aluminum foil with a purity of 99.95% was used as a substrate for pretreatment. The specific method was as follows: the aluminum foil was immersed in a sodium hydroxide solution for 20 seconds, and then washed with water until neutral to remove the oxide layer on the surface of the aluminum foil, thereby obtaining the pretreated aluminum foil;

[0041] The concentration of the sodium hydroxide solution described in step 1 is 40g / L;

[0042] The temperature of the sodium hydroxide solution described in step 1 is 80° C.

[0043] 2. Preparation of zinc immersion solution:

[0044] Mixing sodium hydroxide, zinc oxide, karaya gum, sodium sulfonamide acetyl and water uniformly to obtain a zinc dipping solution;

[0045] The concentration of sodium hydroxide in the zinc leaching solution described in step 2 is 500 g / L, the concentration of zinc oxide is 100 g / L, the concentration of karaya gum is 3 g / L, and the concentration of sodium sulfacetyl acetate is 1.5 g / L;

[0046] 3. Zinc treatment:

[0047] The pretreated aluminum foil was immersed in a zinc dipping solution for 2 seconds, washed with water three times, and dried to obtain a zinc-dipped aluminum foil negative electrode for lithium-ion batteries (denoted as Al@Zn-2s);

[0048] The temperature of the zinc immersion solution in step 3 is 25°C;

[0049] The drying temperature in step 3 is 60° C. and the drying time is 1 h.

[0050] Example 2: A method for preparing a zinc-impregnated aluminum foil negative electrode for a lithium-ion battery is specifically completed by the following steps:

[0051] 1. Pretreatment of aluminum foil:

[0052] Aluminum foil with a purity of 99.95% was used as a substrate for pretreatment. The specific method was as follows: the aluminum foil was immersed in a sodium hydroxide solution for 20 seconds, and then washed with water until neutral to remove the oxide layer on the surface of the aluminum foil, thereby obtaining the pretreated aluminum foil;

[0053] The concentration of the sodium hydroxide solution described in step 1 is 40g / L;

[0054] The temperature of the sodium hydroxide solution described in step 1 is 80° C.

[0055] 2. Preparation of zinc immersion solution:

[0056] Mixing sodium hydroxide, zinc oxide, sodium potassium tartrate, azodicarbonamide, β-cyclodextrin and water uniformly to obtain a zinc immersion solution;

[0057] The concentration of sodium hydroxide in the zinc leaching solution described in step 2 is 500 g / L, the concentration of zinc oxide is 100 g / L, the concentration of potassium sodium tartrate is 2.5 g / L, the concentration of azodicarbonamide is 0.5 g / L, and the concentration of β-cyclodextrin is 0.8 g / L;

[0058] 3. Zinc treatment:

[0059] The pretreated aluminum foil was immersed in a zinc dipping solution for 5 seconds, washed with water three times, and dried to obtain a zinc-dipped aluminum foil negative electrode for lithium-ion batteries (denoted as Al@Zn-5s);

[0060] The temperature of the zinc immersion solution in step 3 is 25°C;

[0061] The drying temperature in step 3 is 60° C. and the drying time is 1 h.

[0062] Comparative Example 1: The difference between this embodiment and embodiment 2 is that in step 2, sodium hydroxide, zinc oxide and water are mixed evenly to obtain a zinc immersion solution;

[0063] The concentration of sodium hydroxide in the zinc leaching solution in step 2 is 500 g / L, and the concentration of zinc oxide is 100 g / L. Other steps and parameters are the same as those in Example 2.

[0064] Figure 1 The morphology of the zinc-impregnated aluminum foil negative electrode and the traditional aluminum foil negative electrode prepared using the additive in Example 1 under an optical microscope;

[0065] from Figure 1 It can be seen that there are many uneven vertical stripes on the surface of the traditional aluminum foil negative electrode, which increases the roughness of the traditional aluminum foil surface, which will make the alloying process of lithium ions on the surface of the traditional aluminum foil uneven, thereby causing uneven stress distribution on the surface of the aluminum foil and causing structural damage. However, the surface of the aluminum foil after zinc immersion using additives in Example 1 is covered with a dense and uniform zinc layer. During the charge and discharge process, the dense zinc layer will promote the uniform alloying of lithium ions on its surface, relieve the structural failure caused by stress, and thus prolong the cycle life.

[0066] Figure 2 The morphology of the zinc-impregnated aluminum foil negative electrode prepared with the additive in Example 2 and the zinc-impregnated aluminum foil negative electrode prepared without the additive in Comparative Example 1 under a scanning electron microscope;

[0067] from Figure 2 It can be seen that the zinc layer of the zinc-impregnated aluminum foil negative electrode prepared using additives in Example 2 is dense, uniform, and has a wide coverage range; while the zinc layer of the zinc-impregnated aluminum foil negative electrode prepared without using additives in Comparative Example 1 is rough and has a small coverage range.

[0068] The zinc-impregnated aluminum foil prepared in Examples 1 and 2, the zinc-impregnated aluminum foil without additives in Comparative Example 1, and the traditional aluminum foil were made into electrode sheets with the same surface area in a punching machine and used as negative electrode materials for lithium-ion batteries.

[0069] According to the button cell assembly structure, the zinc-impregnated aluminum foils prepared in Examples 1 and 2 after punching, the zinc-impregnated aluminum foil without additives in Comparative Example 1, the conventional aluminum foil and the lithium foil were assembled into half-cells; in the constant current mode, 0.5 mA / cm 2 The current density is charged to 2.0 mAh / cm 2 The capacity load is set to 0.9V and the discharge end voltage is limited to 0.9V. Figure 3 , Figure 4 As shown;

[0070] Figure 3 The half-cell assembled with the zinc-impregnated aluminum foil negative electrode prepared using the additive in Example 1 was 2 and 2.0mAh / cm 2 Cyclic performance curve under capacity load;

[0071] from Figure 3 It can be seen that the zinc-impregnated aluminum foil negative electrode prepared using the additive in Example 1 can be stably cycled up to 450 cycles while maintaining a high average coulomb efficiency of 96.85%.

[0072] Figure 4 The half-cell assembled with the zinc-impregnated aluminum foil negative electrode prepared with the additive of Example 2 and the conventional aluminum foil negative electrode at 0.5 mA / cm 2 and 2.0mAh / cm 2 The charge-discharge curve and cycle performance curve under the capacity load of ; in the figure, a and d are half-cells assembled using traditional aluminum foil, b and e are half-cells assembled using zinc-impregnated aluminum foil without additives in Comparative Example 1, and c and f are half-cells assembled using zinc-impregnated aluminum foil prepared in Example 2;

[0073] from Figure 4 It can be seen that the half-cell of the zinc-impregnated aluminum foil negative electrode prepared using the additive of Example 2 has a charge-discharge voltage difference of 50 mV less than that of the half-cell of the conventional aluminum foil and the zinc-impregnated aluminum foil negative electrode without the additive at the 10th cycle, which indicates that the zinc-impregnated aluminum foil negative electrode has a smaller impedance. In addition, from the cycle curve, the cycle life of the zinc-impregnated aluminum foil negative electrode prepared using the present invention is about 300 cycles, while the conventional aluminum foil negative electrode can only cycle about 170 cycles, and the zinc-impregnated aluminum foil without the additive is about 275 cycles, which indicates that the dense and compact zinc-impregnated layer prepared by the present invention can effectively prevent the aluminum foil negative electrode from failing during the cycle process, so that the aluminum foil negative electrode has more stable electrochemical properties and a longer cycle life.

Claims

1. A method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries, characterized in that The preparation method is specifically completed according to the following steps:

1. Pretreatment of aluminum foil: The aluminum foil is immersed in a sodium hydroxide solution for a period of time, and then taken out and washed with water until it is neutral to remove the oxide layer on the surface of the aluminum foil to obtain a pretreated aluminum foil; 2. Preparation of zinc immersion solution: Evenly mixing sodium hydroxide, zinc oxide, additives and water to obtain a zinc dipping solution; 3. Zinc treatment: The pretreated aluminum foil is immersed in a zinc dipping solution for a period of time, taken out, washed with water, and dried to obtain a zinc-dipped aluminum foil negative electrode for lithium-ion batteries.

2. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The soaking time described in step 1 is 20s to 40s.

3. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The concentration of the sodium hydroxide solution described in step 1 is 40g / L to 50g / L.

4. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The temperature of the sodium hydroxide solution described in step 1 is 80°C.

5. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The concentration of sodium hydroxide in the zinc leaching solution described in step 2 is 400g / L to 500g / L, the concentration of zinc oxide is 50g / L to 100g / L, and the concentration of the additive is 0.05g / L to 5g / L.

6. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The additive in step 2 is a mixture of two or more of potassium sodium tartrate, karaya gum, sodium sulfonamide acetyl, β-cyclodextrin, azodicarbonamide and 4-hexylresorcinol.

7. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The soaking time described in step 3 is 2s to 40s.

8. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The temperature of the zinc dipping solution described in step 3 is 25°C.

9. The method for preparing a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries according to claim 1, characterized in that The number of water washing in step 3 is 2 to 4 times; the drying temperature in step 3 is 60° C., and the drying time is 1 hour.

10. Application of a zinc-impregnated aluminum foil negative electrode for lithium-ion batteries prepared by the preparation method according to claim 1, characterized in that A zinc-impregnated aluminum foil negative electrode applied to a lithium-ion battery is used as the negative electrode of the lithium-ion battery.

Citation Information

Patent Citations

  • Method for protecting anode of lithium sulfur battery

    CN105140449A

  • Secondary battery and preparing method thereof

    CN106340651A

  • Lithium ion battery, preparation method thereof and application of porous aluminum-carbon composite material

    CN109713289A

  • Aluminum-based zinc negative electrode material and preparation method and application thereof

    CN117410433A

  • Current collector for lithium ion batteries

    CN1195899A